Application of a Preventive Training Program Implementation Framework to Youth Soccer and Basketball Organizations - Root, Hayley J. (J Athl Train, 2019)
CONTEXT: Preventive training programs (PTPs) can reduce injury rates and improve neuromuscular control and sport performance. However, PTPs must be implemented correctly and consistently over time for athletes to benefit. Coaches represent the best long-term option for implementing PTPs. Youth athletes are at the optimal age for developing good habits before maturation. Although frameworks have been proposed to guide implementation efforts, little is known regarding the feasibility and real-world context of PTP implementation at the youth sport level. OBJECTIVE: To evaluate the application of the 7-Step framework for promoting implementation of a preseason PTP workshop. DESIGN: Descriptive epidemiology study. SETTING: Youth soccer and basketball organizations. PATIENTS OR OTHER PARTICIPANTS: Organizations with at least 1 team of athletes aged 8 to 14 years were invited to participate in a free preseason coaches' education workshop on PTP implementation. INTERVENTION(S): The 7-Step framework was used to guide PTP education and implementation for each organization. Personnel at organizations that agreed to participate attended a single preseason workshop for coaches. Research staff were available as a resource throughout the season but did not actively implement or monitor the PTPs. MAIN OUTCOME MEASURE(S): Retrospective evaluation of each organization's completion of steps 1 through 5 of the 7-Step framework. RESULTS: A total of 62 youth soccer (n = 40) and basketball (n = 22) organizations were invited to participate. Twelve organizations completed steps 1 through 4 and steps 5a through 5d. The highest drop-off rate occurred during step 1, “Establishing Administrative Support.” No organization completed all components of steps 1 through 5. CONCLUSIONS: To better understand how to successfully promote PTP adoption, we must identify the implementation steps that may present the most challenges. Because the highest drop-off rate was seen during the initial step, establishing administrative support and strengthening initial engagement are necessary to improve PTP implementation.